Financial technologies (FinTech) for mental health: The potential of objective financial data to better understand the relationships between financial behavior and mental health - Blair, Johnna; Brozena, Jeff; Matthews, Mark; Richardson, Thomas; Abdullah, Saeed (Frontiers in Psychiatry, 2022)
The relationship between mental health and financial difficulties is complex. Those living with mental illnesses are at increased risk of financial hardships and debt-related stress. This can be further complicated by a range of problematic financial behaviors related to specific mental health symptoms, such as impulsive purchasing or missing deadlines. While previous studies have resulted in valuable insights on how mental health symptoms can manifest in specific financial behaviors, they might not lead to the complete picture given their reliance on self-reported perceptions of individual’s own behaviors. In other words, self-reported data can suffer from incomplete recall and other biases, particularly during symptomatic periods. Being able to access objective personal financial data can help to address this issue. Recent increased digitization of banking services have made fine grained personal financial data more accessible than ever before. By leveraging this objective financial data, we can more easily investigate this relationship — the ebb and flow of finances and mental health. In this paper, we present novel research methods for collecting and analyzing personal financial data alongside mental health factors, illustrated through a N=1 case study using data from one individual with bipolar disorder. While we have not found statistically significant trends nor our findings are generalizable beyond this case, our approach provides an insight into the challenges of accessing objective financial data. We outline what data is currently available, what can be done with it, and what factors to consider when working with financial data. More specifically, using these methods researchers might be able to identify symptomatic traces of mental ill health in personal financial data such as identifying early warning signs and thereby enable preemptive care for individuals with serious mental illnesses. Based on this work, we have also explored future directions for developing interventions to support financial wellbeing. Furthermore, we have described the technical, ethical, and equity challenges for financial data-driven assessments and intervention methods, as well as provided a broad research agenda to address these challenges. By leveraging objective, personalized financial data in a privacy-preserving and ethical manner help lead to a shift in mental health care.